2020
DOI: 10.1101/2020.08.06.20169573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial effects of colchicine for moderate to severe COVID-19: an interim analysis of a randomized, double-blinded, placebo controlled clinical trial

Abstract: Introduction. Neutrophilia and high levels of proinflammatory cytokines and other mediators of inflammation are common finds in patients with severe acute respiratory syndrome due to COVID-19. By its action on leukocytes, we propose colchicine as an intervention worthy of being tested. Objective. To evaluate whether the addition of colchicine to standard treatment for COVID-19 results in better outcomes. Methods. We present the interim analysis of a single-center randomized, double-blinded, placebo controlled … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 25 publications
5
54
0
13
Order By: Relevance
“…72 A third prospective study randomised 38 hospitalised COVID-19 patients to colchicine or placebo in a double-blinded manner. 73 Patients receiving colchicine had less need for supplemental oxygen at day 7 (6% vs 39%) and were more likely to be discharged at day 10 (94% vs 83%). Colchicine subjects also had greater reduction of CRP, and no increase in serious adverse events.…”
Section: Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…72 A third prospective study randomised 38 hospitalised COVID-19 patients to colchicine or placebo in a double-blinded manner. 73 Patients receiving colchicine had less need for supplemental oxygen at day 7 (6% vs 39%) and were more likely to be discharged at day 10 (94% vs 83%). Colchicine subjects also had greater reduction of CRP, and no increase in serious adverse events.…”
Section: Reviewmentioning
confidence: 94%
“…Colchicine subjects also had greater reduction of CRP, and no increase in serious adverse events. 73 Additional inpatient studies are ongoing (online supplemental table 2). Although the permitted use of other treatments could have biased the impact of colchicine in these studies, in the GRECO-19 trial no glucocorticoids were administered and other medications did not differ between the two groups; in the Italian study, there was no difference in outcomes among patients given colchicine who did or did not also receive dexamethasone.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 112 articles were screened, 106 were excluded since they did not meet inclusion criteria ( Figure 1 ). A total of six studies, four published after peer-review 7 , 9 , 10 , 11 and two pre-prints 12 , 13 including 881 patients with confirmed COVID-19 were evaluated, 406 of whom were treated with colchicine in addition to standard-of-care ( Table ). To address one study 12 that reported no events in both arms, a value of 0.5 was added to the respective cells.…”
mentioning
confidence: 99%
“…A total of six studies, four published after peer-review 7 , 9 , 10 , 11 and two pre-prints 12 , 13 including 881 patients with confirmed COVID-19 were evaluated, 406 of whom were treated with colchicine in addition to standard-of-care ( Table ). To address one study 12 that reported no events in both arms, a value of 0.5 was added to the respective cells. 14 The pooled odds ratio for mortality was 0.35 (95% confidence interval 0.24-0.52) and a similar significant trend was observed in terms of the risk difference ( Figure 2 A).…”
mentioning
confidence: 99%
See 1 more Smart Citation